Estimation of Pyrazinamide, Isoniazid and Rifampicin in Pharmaceutical Formulations by High Performance Liquid Chromatography Method - GUNASEKARAN, S.; SAILATHA, E. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance liquid chromatography (HPLC) method has been adopted for the estimation of pyrazinamide, isoniazid and rifampicin in bulk and pharmaceutical formulations. Simultaneous estimation of pyrazinamide and isoniazid in their pharmaceutical dosage form has been developed using RP-C18 column. The mobile phase containing water, monobasic potassium dihydrogen orthophosphate and acetonitrile buffer was pumped at a flow rate of 1.5 mL/min and the UV detection was carried out at 254 nm. Similarly, estimation of rifampicin was carried out with a mobile phase containing water, acetonitrile, methanol, citric acid and sodium periodate using RP-C8 column. The mobile phase was pumped at a flow rate of 1.2 mL/min and the UV detection was carried out at 254 nm. Retention times for pyrazinamide, isoniazid and rifampicin are about 6.307, 4.763 and 5.124 min, respectively. The study shows that the method is accurate, linear, simple and reproducible for checking the quality of the drug.